Mechanisms of Autophagy in Metabolic Stress Response. Issue 1 (3rd January 2020) - Gross, Angelina S.; Graef, Martin
Abstract: Autophagy is a highly conserved catabolic pathway critical for stress responses and the maintenance of cellular homeostasis. Defective autophagy contributes to the etiology of an increasing number of diseases including cancer, neurodegeneration, and diabetes. Cells have to integrate complex metabolic information in order to counteract metabolic challenges ranging from carbon, nitrogen, and phosphate to metal ion limitations. An unparalleled variety of cytoplasmic materials in size and nature can be transported into the lytic compartment for degradation and recycling by transient double-membrane compartments, termed autophagosomes, during macroautophagy. In this review, we will outline our current mechanistic understanding of how cells regulate the initiation of macroautophagy to target substrates nonselectively or selectively. With an emphasis on findings in the yeast system, we will describe the emerging principles underlying the regulation of autophagy substrate recognition, which critically shapes the scope of stress-adapted autophagy responses upon diverse metabolic challenges. Graphical abstract: Image 1 Highlights: We review the molecular mechanisms of macroautophagy. We describe the current understanding of nonselective and selective autophagy induction. We review the multilayered mechanisms of substrate regulation for the examples of mitophagy, ribophagy, and proteaphagy. We summarize our current understanding of composite autophagy responses in response to different metabolic challenges.